Light ion isotope identification in space using a pixel detector based single layer telescope - Kroupa, M.; Bahadori, Amir A.; Campbell-Ricketts, T.; George, S. P.; Stoffle, N.; Zeitlin, C. (My University, 2018)
It is demonstrated that modern pixel detectors can be utilized as single-layer particle telescopes, offering details of a particle's stopping power evolution surpassing those provided by multi-layer, non-pixelated instruments. For particles that stop in the detector, this advantage arises from repeatably sampling the Bragg curve: we always know which part of the Bragg peak was measured. We can then create a dE/dx1 vs dE/dx2 plot where the stopping power at the beginning and the end of the track is compared. We are able to identify and analyze several fine-grained features on such plots, including several related to particles that stop inside the detector, termed “stopping.” Using data from an instrument aboard the International Space Station, we show that different isotopes of stopping hydrogen can be identified as their stopping powers differ. Other features of the dE/dx1 vs dE/dx2 plot not resolvable in multi-layer particle telescopes are also exhibited, such as nuclear interactions that occur within the sensor active volume.
Citation: Kroupa, M., Bahadori, A. A., Campbell-Ricketts, T., George, S. P., Stoffle, N., & Zeitlin, C. (2018). Light ion isotope identification in space using a pixel detector based single layer telescope. Applied Physics Letters, 113(17), 174101. https://doi.org/10.1063/1.5052907